Territorial Anatomy. Alternatives to activate the otherness of Potosí colonial paintings - Godoy Vega, Francisco Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2012)
From the images of allegories and unknown geographies, the representation of the American territory is made in an overlapped form with the body in a particular typeof erotic-politics. The case of the representation of the Villa Imperial de Potosí is paradigmatic in this subject as it generated an iconography that passed from therepresentation of its hill like generator of structures class/ race to its union with the virgin. Here two works of the city built in the irst half of the 18th century are studied -after the decay of the economy of one of the greatest cities of the world at that time - that in addition are found in Spanish public collections, to try at the time how thisdimension of unit between body and territory articulates within them. To inish, some expositive contexts are shown in which the same ones have been presented andpossible alternatives to think the curatorial activation and criticism of these images.